Social Transformation of the Community to Children's Education in Schools - Darman Manda; Dyan Paramitha Darmayanti; Iqbal Arifin (Universitas Sulawesi Barat, 2026)
Social transformation has influenced changes in people's perceptions of children's education in schools. Education is no longer understood solely as a formal activity but is increasingly seen as an important part of improving the quality of life and the family's future. This study aims to analyze social transformation towards children's education in schools. The research uses a qualitative, descriptive approach. The research was conducted in Minasa Upa Village, Rappocini District, Makassar City, and involved eight informants selected using purposive sampling. Data collection is conducted through observation, in-depth interviews, and documentation. Data analysis uses the Miles and Huberman model, with a Bourdieu perspective, particularly the concepts of habitus and cultural capital. The study's results show that the community has changed its view of children's education in schools. Education is no longer understood as just a formal obligation but is beginning to be seen as cultural capital that influences children's futures and the quality of family life. Social transformation is influenced by technological and information developments, parents' life experiences, the community's social environment, and the family's economic conditions. This research shows that education has become an important part of modern society's social strategy to expand families' social and economic opportunities.